Selection of Public Servants into Politics - Thomas Braendle; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2011)
Countries differ substantially in how they deal with politicians that come from the public sector. Most constitutions include incompatibility and ineligibility rules due to concerns about conflicts of interest and the politicization of the public service. We study how these rules affect the attractiveness of parliamentary mandates for public servants and thus the selection into politics. We compile a novel dataset that captures the fraction of public servants in 71 national legislatures as well as the respective (in)compatibility regimes. On average, there are 7 percentage points fewer public servants in parliaments where a strict regime is in force. Supplementary evidence shows that the fraction of public servants in parliament is positively correlated with government consumption as well as the absence of corruption.
Keywords: D72; K39; 330; Political selection; public servants; incompatibility; political representation; corruption; government consumption; Öffentlicher Dienst; Arbeitsplatzwechsel; Parlament; Korruption; Neue politische Ökonomie